Educação ambiental e formação de professores para a conservação da fauna do Parque Estadual das Fontes do Ipiranga (PEFI - SP) - Silva, Nathália Formenton da (2018)
The Fontes do Ipiranga State Park (PEFI) is an Atlantic Forest Conservation Unit (UC) located in the city of São Paulo and has a unique feature: it houses several institutions in its interior, such as the São Paulo Zoo and the São Paulo Botanic Garden (JB), among others. The PEFI presents more than 210 species of vertebrates, however, much of this fauna is threatened by anthropic actions because it is inserted in an urban area. Some problems are: the risk of running over, electrocution, illegal hunting / capture and transmission of diseases and predation by invading domestic animals. Our main objective was to elaborate and apply a teacher education course, from a critical, emancipatory and transformative environmental education (EE) perspective, to two schools located around the PEFI, in order to identify the dimensions of the educational process, the dimensions of social learning (AS), in addition to the EE aspects. The research was developed in a qualitative approach, based on the presuppositions of action research. Thus, we signed a partnership with two state schools, one elementary school I and another elementary and secondary school, in which 47 teachers from all areas of knowledge participated. The research had a procedural character, being developed in four moments: the first consisted of a socio-environmental diagnosis with the participants; the second was the preparation of the course based on the diagnosis data, meeting all the demands of teachers and schools; the third time consisted of the application of the course, which had a total of 20 hours, being 8 presential and 12 at a distance, with development of EE activities in schools and student visits to the São Paulo Zoo; the last moment of the research was the analysis of the data and the course. As a result, we identify all dimensions of the educational process: the dimension of knowledge, ethical and aesthetic values and participation, the first one prevailing, but also the dimension of participation was well considered. As regards AS, its dimensions - reflection, communication, negotiation, action and participation - were also identified, which allowed us to relate both theoretical references in a critical EE perspective. Also with the course analysis, we could note that, although this was based on critical EE, the EE strand that was most identified in the course was pragmatic EE, which did not exclude the other strands and, in some aspects, the conservative and critical lines emerged. In this way, the training course addressed the main characteristics of effective continuing education courses, including, in part, pedagogical knowledge of content, active learning methods, collective participation, duration and coherence. Thus, we hope the course has contributed to the awareness of those involved, so that they become interested in the environmental issues of PEFI and become involved in the fight for the conservation of this UC.